AB0051 Asymptomatic hyperuricemia and markers of inflammation. (23rd January 2014) - Petrova, M.; Mazurov, V.; Shemerovskaya, T.; Zacharova, G.; Gudkova, A.
Abstract : Background: The development of inflammation induced by sodium monourata crystals is characterized by increased levels of an entire variety of cytokines. Therefore it can be assumed that some of them could become markers of the transition of asymptomatic hyperuricemia into a gout. Then an inflammation could be ceased at the earliest stages. Objectives: To identify the possible immunological markers of transition of an asymptomatic hyperuricemia into a gout. Methods: 376 patients with a gout and 322 patients with an asymptomatic hyperuricemia were included and prospectively observed (from 2007 to 2011) at the Clinical Centre of a gout treatment (St.-Petersburg, Russia). Cytokine profile was examined among 97 patients (a main group) a control group consisted of 13 healthy volunteers. The main group included 35 patients with a chronic gout (1 st group), 28 - with an acute one (2 nd group), 3 rd group consisted of 34 patients with asymptomatic hyperuricemia, among which 14 patients debuted with an acute attack of the gout during the observation period (3 rd -A group), in 20 patients the hiperuricemia remained asymptomatic (3 rd -B group) Cytokine profile was assessed using a flowing laser immunoanalyze Bio-Plex 3D. Data processing and analysis were performed by the program «STATISTICA 7.0 "(by StatSoft, Inc.). A nonparametric model was used as well: the Mann-Whitney U test for pair-wise group comparison. The data had preliminarily been logarithmed in order to achieve greater veracity of the obtained results. Results: A significant increase of cytokine levels was detected among the patients in the 3 rd group compared to the control group: IL-8 (14.74 and 1.00, respectively, p = 0.005), GM-CSF (6.11 and 0.00 respectively, p = 0.00001), TNF-α(4.54 and 0.09, respectively, p = 0.00002). A higher level of GM-CSF was registered in patients of the 3 rd group compared to the 1 st group (6.11 and 3.69 respectively, p < 0.05). An increase of IL-8 levels was originally registered among the patients of the 3 rd -A group compared to the 3 rd -B group (54.58 and 14.74 respectively, p < 0.05) and TNF-α(14.06 and 4.54 respectively, p < 0.05). In addition, an increase of cytokines levels was observed in group 3-B versus group 1: IL-8 (54.58 and 22.10 respectively, p < 0.05), GM-CSF (3.69 and 6.64 respectively, p < 0.05), and TNF-α (5.39 and 14.06 respectively, p < 0.05). The differences between the levels of cytokines were detected after comparison of the 2 nd and the 1 st group: IL-6 (11.59 and 0.00, respectively p and 11.59 < 0.05), IL-8 (109.35 and 22.10 respectively, p < 0.05), GM-CSF (5.88 and 3.69 respectively, p < 0.05) and TNF-α (20.01 and 5.39 respectively, p < 0.05). Conclusions: Increased levels of IL-8, GM-CSF, TNF-α in patients with asymptomatic hyperuricemia could be a predictor of development of gout and a possible target for therapeutic interventions. Disclosure of Interest: None Declared